Correlation between wastewater and COVID-19 case incidence rates in major California sewersheds across three variant periods - Angela Rabe; Sindhu Ravuri; Elisabeth Burnor; Joshua A. Steele; Rose S. Kantor; Samuel Choi; Stanislav Forman; Ryan Batjiaka; Seema Jain; Tomás M. León; Duc J. Vugia; Alexander T. Yu (IWA Publishing, 2023)
Monitoring for COVID-19 through wastewater has been used for adjunctive public health surveillance, with SARS-CoV-2 viral concentrations in wastewater correlating with incident cases in the same sewershed. However, the generalizability of these findings across sewersheds, laboratory methods, and time periods with changing variants and underlying population immunity has not been well described. The California Department of Public Health partnered with six wastewater treatment plants starting in January 2021 to monitor wastewater for SARS-CoV-2, with analyses performed at four laboratories. Using reported PCR-confirmed COVID-19 cases within each sewershed, the relationship between case incidence rates and wastewater concentrations collected over 14 months was evaluated using Spearman's correlation and linear regression. Strong correlations were observed when wastewater concentrations and incidence rates were averaged (10- and 7-day moving window for wastewater and cases, respectively, ρ = 0.73-0.98 for N1 gene target). Correlations remained strong across three time periods with distinct circulating variants and vaccination rates (winter 2020-2021/Alpha, summer 2021/Delta, and winter 2021-2022/Omicron). Linear regression revealed that slopes of associations varied by the dominant variant of concern, sewershed, and laboratory (β = 0.45-1.94). These findings support wastewater surveillance as an adjunctive public health tool to monitor SARS-CoV-2 community trends. HIGHLIGHTS Wastewater and incidence rate correlations were strong throughout three variant periods of the COVID-19 pandemic and spanning vaccine introduction to widespread uptake.; Correlations persisted across different regions of California with four unique labs.; Slopes of associations between wastewater concentration and case varied by the variant, sewershed, and laboratory.; Wastewater is a complementary COVID-19 public health tool.;